Enhancing High-Order Above-Threshold Dissociation of H+2 Beams with Few-Cycle Laser Pulses - McKenna, J.; Sayler, A. M.; Anis, F.; Gaire, B.; Johnson, Nora G.; Parke, E.; Hua, J. J.; Mashiko, H.; Nakamura, C. M.; Moon, E.; Chang, Z.; Carnes, K. D.; et al. (My University, 2008)
High-order (three-photon or more) above-threshold dissociation (ATD) of H+2 has generally not been observed using 800 nm light. We demonstrate a strong enhancement of its probability using intense 7 fs laser pulses interacting with beams of H+2, HD+, and D+2 ions. The mechanism invokes a dynamic control of the dissociation pathway. These measurements are supported by theory that additionally reveals, for the first time, an unexpectedly large contribution to ATD from highly excited electronic states.